Instilling Religious and Honest Character Education at MIN 3 Jombang: Using the Hompimpa Alaium Gambreng Game - Yurissa, Putri Norma (ETDC: Indonesian Journal of Research and Educational Review, 2022)
This article discusses the character building of madrasa students through the traditional game of Hompimpa Alaium Gambreng. The purpose of this study was to analyze the effect of the Hompimpa Alaium Gambreng game on changes in the character of students, especially religious characters and honesty. This study uses a mixed approach, namely quantitative and qualitative. According to the results of the research conducted, the Hompimpa Alaium Gambreng game seems to have a significant impact on the cultivation of religious character and honesty. Another benefit of this research is that it can introduce Indonesian traditional culture to students so that it is not forgotten and there are many character values in it. The cultivation of character education requires commitment, continuity, and cooperation between teachers and parents so that the formation of religious character and honesty is not only discourse and can underlie students' ability to achieve superior human resources.